Romanillos guitarrero - Herranz, David; Romanillos, Raúl (Gettysburg, 2015)
A journey through the life and work of José Luis Romanillos, Spanish self-taught guitar builder. He emigrates to England looking for a job and there, following manual instructions, he manages to make his first guitar. Back in Spain after retirement, he introduces us to the old art of guitar construction. Possibly, we have attended the last guitar that has come out of his hands, which celebrates the 50 years of his life with Marian. --